Quantifying the economic costs of power outages owing to extreme events: A systematic review - Ghodeswar, Archana; Bhandari, Mahabir; Hedman, Bruce (Renewable & sustainable energy reviews, 2025)
Quantifying the economic cost of long-duration power outages is crucial to justifying investments in resiliency and reliability improvements. However, extensive study on the subject complicates the identification of power outage costs and determining the most suitable approach to quantify them for an individual, specific facility, particularly in the context of extreme events. This research provides a systematic review of economic studies estimating the impact of environmental disasters at the microeconomic and macroeconomic levels. Of 326 articles, evaluating the costs of power outages in extreme events, this work identified 22 studies that attempted to quantify the economic costs. These findings indicate that quantifying power outage costs lacks standardization, posing challenges for comparing different studies. Most analyses aiming to quantify these costs for utilities, sectors, and the overall economy rely on outdated survey data, which offer generalized rather than specific cost estimations. The costs of power outages exhibit a significant dependence on factors such as the sector involved, the type of customer affected, and the outage duration. To quantify industry costs, the research in this study suggests that using the National Renewable Energy Laboratory's online, open-access Customer Damage Function Calculator is the best option for individual-level assessments of industries, hospitals, offices, education centers, and similar facilities. However, the Interruption Cost Estimate Calculator can estimate outage costs across industrial, commercial, and residential sectors for macroeconomic outcomes. Finally, this article discusses the relative strengths of these methods and tools and the potential directions for future research. [Display omitted] •Power outage costs vary based on sector, customer type, and duration.•Standard quantifying units, updated surveys, and granular outage data are required.•The Interruption Cost Estimate Calculator is better suited for macroeconomic costs.•The Customer Damage Function Calculator is better suited for individual consumers.•Quantifying outage costs justifies investments in renewable and sustainable power.